Epigenetic alterations in human brain tumors in a Brazilian population - ANSELMO, Nilson Praia (2014)
Aberrant methylation of CpG islands located in promoter regions represents one of the major mechanisms for silencing cancer-related genes in tumor cells. We determined the frequency of aberrant CpG island methylation for several tumor-associated genes: DAPK, MGMT, p14ARF, p16INK4a, TP73, RB1 and TIMP-3 in 55 brain tumors, consisting of 26 neuroepithelial tumors, 6 peripheral nerve tumors, 13 meningeal tumors and 10 metastatic brain tumors. Aberrant methylation of at least one of the seven genes studied was detected in 83.6% of the cases. The frequencies of aberrant methylation were: 40% for p14ARF, 38.2% for MGMT, 30.9% for, p16INK4a, 14.6% for TP73 and for TIMP-3, 12.7% for DAPK and 1.8% for RB1. These data suggest that the hypermethylation observed in the genes p14ARF, MGMT and p16INK4a is a very important event in the formation or progression of brain tumors, since the inactivation of these genes directly interferes with the cell cycle or DNA repair. The altered methylation rate of the other genes has already been reported to be related to tumorigenesis, but the low methylation rate of RB1 found in tumors in our sample is different from that so far reported in the literature, suggesting that perhaps hypermethylation of the promoter is not the main event in the inactivation of this gene. Our results suggest that hypermethylation of the promoter region is a very common event in nervous system tumors.